Clinical experience of baclofen in alcohol dependence: A chart review - Rozatkar, Abhijit R. (Ind Psychiatry J, 2016)
INTRODUCTION: Craving is recognized as a formidable barrier in the management of patients with alcohol dependence. Among pharmacological agents that have been used in experimental studies for reduction in craving, baclofen appears to have a significant advantage over other agents. METHODOLOGY: The study is retrospective chart review of patients (n = 113) who have been treated with baclofen for alcohol dependence in a tertiary hospital of North India. Baseline assessments included sociodemography, motivation, quantity-frequency of alcohol use, and other alcohol-related clinical parameters. Weekly assessments, for a period of 4 weeks, were extracted from records which included dose of baclofen, craving intensity, and alcohol consumption. RESULTS: The study sample was predominantly male, mean age of 41.49 (±9.75) years, most having a family history of substance use (70.97%), and many reporting binge use pattern in last year (49.46%). Baseline assessment revealed 48.7% of the sample was in precontemplation phase for alcohol use and 70% reported severe and persistent craving. This persistent craving was reported by only 15% of the sample by the end of 4 weeks treatment with baclofen (20–40 mg/day). Thirty-four percent of patients reported continued problematic use of alcohol by the end of 4 weeks. CONCLUSION: Our clinical experience suggests that baclofen reduces craving and alcohol consumption including in those with poor motivation. The drug causes few side effects and does not add to the intoxication effect of alcohol. Considering that baclofen is safe in those with liver cirrhosis and reduces withdrawal symptoms due to alcohol, a controlled trial comparing it with standard treatment is required.